Analysis of the Effect of Training, Communication, and Work Motivation on Productivity at PT. Global Mitra Prima - Yusril Mahendra Tanjung; Teguh Wahyono; Kholilul Kholik (Jurnal Fokus Manajemen, 2026)
This study was conducted at PT. Global Mitra Prima with the aim of analyzing the effects of training, communication, and work motivation on employee work productivity. The phenomenon observed in the company indicates that employee productivity in the sales department during the period 2018–2023 experienced an unstable downward trend, suggesting that not all employees were able to perform their duties productively. The population of this study consisted of 48 employees working at the company, and the sampling technique used was a saturated sampling method, resulting in a total sample of 48 respondents. The type of data used was primary data, while the data sources included secondary data. Data collection techniques comprised literature review, surveys, and observation. The data analysis techniques applied included multiple regression analysis, classical assumption tests, and hypothesis testing. The results of the study show that training, communication, and work motivation, both partially and simultaneously, have a positive and significant effect on employee productivity in carrying out their tasks. There is a very strong relationship between training and employee work productivity in performing tasks within the company. Employee productivity at the company can be explained by the variables of training, communication, and work motivation by 81.4%, while the remaining 18.6% is explained by other variables not examined in this study